2021
DOI: 10.3174/ajnr.a7266
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Role of Diffusion-Weighted and Dynamic Contrast-Enhanced Perfusion MR Imaging in Paragangliomas and Schwannomas in the Head and Neck

Abstract: BACKGROUND AND PURPOSE: Distinguishing schwannomas from paragangliomas in the head and neck and determining succinate dehydrogenase (SDH) mutation status in paragangliomas are clinically important. We aimed to assess the clinical usefulness of DWI and dynamic contrast-enhanced MR imaging in differentiating these 2 types of tumors, as well as the SDH mutation status of paragangliomas. MATERIALS AND METHODS:This retrospective study from June 2016 to June 2020 included 42 patients with 15 schwannomas and 27 parag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…Regarding DWI analysis, the ADC value can represent cellularity and internal structure and can be used for assessing tumor differentiation and gene mutation status 13 . In this study, normalized mean ADC was significantly higher in the sporadic VSs than in the NF2‐related VSs.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Regarding DWI analysis, the ADC value can represent cellularity and internal structure and can be used for assessing tumor differentiation and gene mutation status 13 . In this study, normalized mean ADC was significantly higher in the sporadic VSs than in the NF2‐related VSs.…”
Section: Discussionmentioning
confidence: 56%
“…10 Diffusion-weighted imaging (DWI) and DCE-MRI have been recently used for differentiation of head and neck tumors and treatment effect assessment. [11][12][13][14] Therefore, in this study we aimed to assess the utility of DWI and DCE-MRI as well as conventional MRI findings for differentiation between sporadic and NF2 VSs and to compare the diagnostic performances between DWI and DCE-MRI.…”
Section: Introductionmentioning
confidence: 99%
“…18 Consistent with the present findings, a separate previous study failed to show any significant difference in ADC values between paragangliomas and schwannomas in the head and neck regions. 14 Abbreviations: AUC, area under the curve; K trans , forward volume transfer constant; NPV, negative predictive value; PPV, positive predictive value; V e , extravascular extracellular space; V p , fractional plasma volume.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the differentiation of head and neck schwannomas and paragangliomas using DWI and DCE-MRI scans; one study has shown that V p may be the most significant parameter in differentiating these lesions. 14 However, the utility of DWI and DCE-MRI scans for differentiating intracranial meningiomas from schwannomas and paragangliomas has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation